Comparing Data Protection and Due Process Implementation in Indonesia - Irawati, Arista Candra; Wijaya, Hendra; Pratama, Ade (Jurnal Ilmiah Dunia Hukum, 2025)
This study aims to analyze and examine legal issues related to personal data protection in Indonesia and Malaysia, as well as to assess the principle of due process of law and its implementation in ensuring legal certainty in personal data protection, particularly in Case No. 46/Pid.Sus/2023/PN.Slt. The research employs an empirical juridical method using statutory, conceptual, and case approaches. The data consist of primary, secondary, and tertiary sources. The findings indicate, first, that both Indonesia and Malaysia are committed to protecting personal data as part of human rights. Indonesia has enacted the Personal Data Protection Law (UU PDP) and its derivatives, while Malaysia has implemented the Personal Data Protection Act 2010. These frameworks demonstrate that both countries possess adequate legal structures to safeguard their citizens’ privacy in the digital era. Second, the application of the due process of law principle in the context of personal data protection—as illustrated in Case No. 46/Pid.Sus/2023/PN.Slt—highlights the importance of transparent, fair, and equitable legal enforcement. The implementation of this principle provides legal certainty for individuals concerning the collection, processing, and protection of their personal data. Upholding due process of law also prevents abuse of authority by law enforcement and ensures that any action taken in handling personal data complies with lawful and accountable procedures.